Biblical folklore - "Vincent, Daniel" (New Delhi, 2007)
This book takes a new Book at the Bible and its people from the dimension of its folk elements. Analysing the Bible from different angles such as the form and contents, it goes into the intricacies of many aspects of people$1 (Bs lives which have moulded their social lifestyles, belief and behaviour. Also, it makes a comprehensive analysis of Biblical riddles, proverbs, folk beliefs, folk gods, folk music and songs, folk medicines and folk games.s
Keywords: Folklore in the bible